2004
DOI: 10.17741/bgsf/76.1-2.005
|View full text |Cite
|
Sign up to set email alerts
|

Pre-1.91 Ga deformation and metamorphism in the Palaeoproterozoic Vammala Migmatite Belt, southern Finland, and implications for Svecofennian tectonics

Abstract: A metamorphic event in the Vammala Migmatite Belt (VMB) at ~1.92 Ga, revealed by SHRIMP U-Pb analyses of both zircon overgrowths and monazite,is interpreted as post-depositional and is correlated with the development of the early high-grade schistosity.Neither this Early Svecofennian deformation and metamorphism, nor the associated complex folding, is present in the overlying Ta mpere Schist Belt (TSB) sequence, consistent with the VMB being part of a pre-1.91 Ga basement complex. The ~1.92 Ga event provides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 58 publications
3
23
0
Order By: Relevance
“…2.0 age group are found in the northern part of the shield, for example in the Korkiavaara arkosite formation in the Peräpohja Schist Belt (Hanski et al, 2005) and in the Tersk Terrane orthogneiss (Daly et al, 2001). The 2.0 Ga age group is common among the detrital grains in meta-greywackes of the Svecofennian formations Claesson et al, 1993;Lahtinen et al, 2002;Rutland et al, 2004). In summary, the major provenance of the LGB is from an unknown 2.0 − 2.1 Ga siliceous igneous terrain suggesting that the LGB is an allochthonous province.…”
Section: Provenance and Age Of Deposition Of The Lgb Metasedimentsmentioning
confidence: 88%
See 1 more Smart Citation
“…2.0 age group are found in the northern part of the shield, for example in the Korkiavaara arkosite formation in the Peräpohja Schist Belt (Hanski et al, 2005) and in the Tersk Terrane orthogneiss (Daly et al, 2001). The 2.0 Ga age group is common among the detrital grains in meta-greywackes of the Svecofennian formations Claesson et al, 1993;Lahtinen et al, 2002;Rutland et al, 2004). In summary, the major provenance of the LGB is from an unknown 2.0 − 2.1 Ga siliceous igneous terrain suggesting that the LGB is an allochthonous province.…”
Section: Provenance and Age Of Deposition Of The Lgb Metasedimentsmentioning
confidence: 88%
“…The youngest detrital zircon grains in the Karelian metasediments are about 1930 ± 24 Ma old, while the oldest are Ar-The Svecofennian formations occupy the central and southwestern part of the shield, more than 350 km SW from the LGB, and are considered a tectonic collage of at least two juvenile arc complexes and a turbidite dominated basin between them (Gaál & Gorbatschev, 1987;Korsman et al, 1997). Sm-Nd and SIMS zircon studies show that an Archaean component may be found in the arc sediments and the majority of detrital zircons are older than 1.9 Ga (Huhma, 1987;Claesson et al, 1993;Lahtinen et al, 2002;Rutland et al, 2004). This may indicate a prolonged arc evolution already before 1.9 Ga or involvement of an unknown (orogenic?)…”
Section: Tectonic Consequences and Correlationmentioning
confidence: 99%
“…Seismically, Bergslagen has also been traced in the middle and lower crust beneath the Ljusdal domain farther north (Korja and Heikkinen, 2005). Andersson (1997), Andersson et al (2004), Bergman et al (2008), Beunk and Page (2001), Hermansson et al (2007Hermansson et al ( , 2008, Högdahl and Sjöström (2001), Högdahl et al (2004), Johansson et al (2006, Krzeminska et al (2009), Lahtinen andNironen (2010), Lahtinen et al (2002Lahtinen et al ( , 2009a, Mansfeld et al (2005), Rutland et al (2001Rutland et al ( , 2004, Stephens et al (2009), Sultan et al (2005, Wikström and Andersson (2004), Williams et al (2008Williams et al ( , 2009). Fe-S-Si indicates the presence of various iron-and sulfide ore deposits.…”
Section: Trans-baltic Palaeoproterozoic Correlations and Tectonic Modmentioning
confidence: 99%
“…In order to explain the "equidimensional" patterns of the continental crust in the Svecofennian orogen, this model has recently been modified by involving orocline tectonics (Beunk and Kuipers, 2012), as well as rotations of primarily linear terranes and their "tectonic wrecks" (Lahtinen et al, 2014). (b) The other group of interpretations, which proposes marginal basin accretion governed by a master subduction zone, has been employed to explain, among other things, the wide distribution of similar populations of detrital zircon and basin formation in the northern and central parts of the Svecofennian orogen in Sweden and Finland at 2.1-1.98, 1.97-1.92, and 1.91-1.86 Ga, while short events of accretion and compression interrupted basin formation at 1.98, 1.92 and 1.88-1.86 Ga (Rutland et al, 2001(Rutland et al, , 2004Williams et al, 2008). A related model, named the "migratory tectonic switching", emphasizes the existence of cycles of alternating extension and compression during the development of the Svecofennian orogen in central Sweden and also elsewhere (Hermansson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Detrital zircon age patterns of the xenoliths in the Vaasa batholith (Kotilainen et al, 2016) are similar to the patterns of previously dated detrital zircon from Svecofennian metasedimentary rocks (cf. Huhma et al, 1991;Claesson et al, 1993;Lahtinen et al, 2002Lahtinen et al, , 2009Rutland et al, 2004;Bergman et al, 2008). Previous U-Pb monazite analyses of the Vaasa batholith have yielded ages between 1872 and 1858 Ma (Alviola et al, 2001;Sipilä et al, 2008).…”
Section: Geologic Settingmentioning
confidence: 98%